General principles of vocational education and training in the tourism education system of the German speaking countries in Western Europe - Samokhval, Olesia; Voinarovska, Natalia (ScienceRise: Pedagogical Education, 2019)
The article deals with the analysis of tourism education systems of the leading countries of Western Europe, namely Germany, Austria, Switzerland and Luxembourg united in the crosslinguistic category of "German-speaking countries". The peculiarities of institutional and disciplinary components of vocational education in tourism are revealed, the educational-qualification levels of the structural model of tourism education are determined and characterized, the main functions of the vocational schools of tourism are defined, and the peculiarities of vocational training of future skilled workers in the specified countries are outlined. It is defined, that the structural model of tourism education in the German-speaking countries includes the pathway of obtaining professional qualifications, different types of educational establishments, a variety of vocational study programs and degree levels. It is appointed, that the predominant advantage of basic tourism education in the German-speaking countries is the dual system of vocational education and training that enables students getting qualifications in the form of apprenticeship working together with enterprise training providers. A distinctive feature of higher tourism education is the binary structure in which the traditional university sector exists concurrently with the non-university higher education sector. It is defined, that the common feature of tourism education systems in German-speaking countries is the flexibility of educational process and the coherence of educational-qualification levels within vocational schools and higher institutions. It is determined, that the compliance with the principles of consistency and continuity, the focus on providing future skilled workers with the opportunity to obtain appropriate vocational training program in compliance with their needs and abilities are the basic principles of lifelong learning in tourism education. It is proved that the intense competition between organizers of tourism education in German-speaking countries contributes to their desire of following strictly the existing international education standards. The constant modernization of the content of vocational education and training, as well as cooperation with the European and non-European educational partners in the higher tourism education sphere intensifies student mobility and academic activity